TAHLILU BUNUD ASILAH MUTA’DDIDAH IKHTIYARAT AL-LUGHAH AL-ARABIYAH: تحليل بنود أسئلة متعددة إختيارات اللغة العربية - Ali Fuddin Nasution; Baiq Laili Rahmawati; Madian Fitri Salma; Nur Qomari; M. Syarifuddin (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Abstract: This study discussesed about the importance of vocabulary analysis in multiple choice, because look at the facts occur, the teacher was asked questions only based on the book without considering whether a different strength, level of difficulty or deceptive force. The purpose of this study was to analyzed in the form of the differential power, difficulty and the deceptive power found among the students of the second grade-A at Khairuddin High School Gondanglegi Malang. This research uses a mixed research method. Data collection methods using documentation and data analysis using content analysis techniques. Data sources in this study are primary data sources in the form of documents on the results of student assessments and secondary data sources in the form of supporting references from research articles and related books. The results of this study are: 1) The discriminatory power of 60% is very low and 40% is low, medium and difficult category must be reviewed but the difficulty without be reviewed. 2) The difficulty level of the questions is 46.66% easy, 26.66% medium, 26.66% difficult. 3) The deceptive power, there was 16 options that were accepted so that they could be used immediately without review. Keywords: Item analysis, test difficulty level, discriminatory power, deceptive power